A benchmark for gel structures: bond percolation enables the fabrication of extremely homogeneous gels - Li, Xiang (Polymer journal, 2021)
Gels are soft-elastic materials consisting of a three-dimensional crosslinked polymer network and liquid filling the space between this network. Numerous gels with unique physical properties have been synthesized and are widely used in our daily lives. However, all of these gels contain a substantial level of structural defects, as detected by scattering measurements. Despite the tremendous efforts made in recent decades to remove imperfections from gels, discernible signs of spatial defects have been persistently observed in gels. Researchers believe that gels are inherently heterogeneous. In this focus review, I briefly introduce a recent finding from our research group’s efforts to fabricate polymer gels free of spatial heterogeneities. The commonly observed scattering profiles for the spatial defects disappeared in the homogeneous gels. The newly observed scattering profiles are a benchmark for gel structures. Despite the tremendous efforts made in recent decades to remove imperfections from gels, discernible signs of spatial defects have been persistently observed in gels. Researchers believe that gels are inherently heterogeneous. In this focus review, I briefly introduce a recent finding from our research group’s efforts to fabricate polymer gels free of spatial heterogeneities via “bond percolation”. The commonly observed scattering profiles for the spatial defects disappeared in the homogeneous gels. The newly observed scattering profiles are a benchmark for gel structures.